2013
DOI: 10.1016/j.molcel.2013.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The Little Elongation Complex Functions at Initiation and Elongation Phases of snRNA Gene Transcription

Abstract: SUMMARY The small nuclear RNA (snRNA) genes have been widely used as a model system for understanding transcriptional regulation due to the unique aspects of their promoter structure, selectivity for either RNA Polymerase (Pol) II or III, and because of their unique mechanism of termination that is tightly linked with the promoter. Recently, we identified the Little Elongation Complex (LEC) in Drosophila that is required for the expression of Pol II-transcribed snRNA genes. Here, using Drosophila and mammalian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(88 citation statements)
references
References 50 publications
6
81
1
Order By: Relevance
“…Since DSIF functions as a dual regulator of transcription elongation for protein-coding genes, it may play a similar role in regulating the U1 gene. It may seem strange that an elongation factor is critical for the synthesis of such a small RNA; however, recent studies have shown that the little elongation complex, which comprises ELL and a few other subunits, is also required for the initiation and elongation phases of snRNA gene transcription 40,41 . It is not immediately clear why elongation factors are required for transcription of short snRNA genes.…”
Section: Discussionmentioning
confidence: 99%
“…Since DSIF functions as a dual regulator of transcription elongation for protein-coding genes, it may play a similar role in regulating the U1 gene. It may seem strange that an elongation factor is critical for the synthesis of such a small RNA; however, recent studies have shown that the little elongation complex, which comprises ELL and a few other subunits, is also required for the initiation and elongation phases of snRNA gene transcription 40,41 . It is not immediately clear why elongation factors are required for transcription of short snRNA genes.…”
Section: Discussionmentioning
confidence: 99%
“…2C; Lin et al 2010). ELL is also found in the little elongation complex (LEC), which specifically regulates distinct stages of small nuclear RNA transcription, essential housekeeping functions that are likely compensated for by the wild-type allele of ELL in leukemia Hu et al 2013b).…”
Section: Mll In Normal Hematopoiesis and In The Transcriptional Elongmentioning
confidence: 99%
“…It has been reported that two ELL/EAF-containing complexes, super elongation complex (SEC) and little elongation complex (LEC), specifically regulate the transcription of distinct genes [4,5]. LEC is composed of multiple subunits including the ELL/EAF component, KIAA0947, NARG2 and ZC3H8 [3,6,7].…”
Section: Transcription Elongation Factors Including Eleven Lysine-ricmentioning
confidence: 99%
“…Recently, we showed that human Mediator subunit MED26 contributes to the recruitment of LEC to a subset of snRNA genes [6]. ICE1 is one of the central components for the assembly of LEC [5]. It has been shown that LEC plays a role in both the transcription initiation and elongation phases of snRNA gene transcription [5].…”
Section: Transcription Elongation Factors Including Eleven Lysine-ricmentioning
confidence: 99%
See 1 more Smart Citation